HUBUNGAN LINGKUNGAN DENGAN PERILAKU SEKS BEBAS REMAJA MAS ALWASHLIYAH INDRAPURA - Siringoringo, Erlina Esther Rotua; Tanjung, Meni Fuzi Astuti; Damanik, Dady Hidayah (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Adolescents are the next generation of the nation, they should be able to protect themselves from doing things that violate expensive norms that have a negative impact on them. The results of interviews conducted with 10 teenagers found that 60% had premaritax and the remaining 40% did not have premarital sex. The research method used in this study is quantitative with a descriptive correlation research design, namely research that describes the circumstances under study in a correlation manner. This study used a cross sectional approach. The population in this study were all MAS AlwashliyahIndrapura class XI students, totaling 65 people. The sample in this study was the entire population as the sample. The results of the study found that the majority of teenagers whose social environment was bad, had free sex, namely 40 people (61.5%), out of a total of 44 people. The majority of adolescents whose social environment is good, do not engage in free sex, as many as 21 people (32.3%), out of a total of 21 people. between the social environment and free sex behavior of Class XI Adolescents at MAS Alwashliyah Indrapura.